2022
DOI: 10.3389/fpsyg.2022.805941
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Discrimination and Everyday Racism Among Children and Adolescents With an Immigrant Background – Results of a Systematic Literature Review on the Impact of Discrimination on the Developmental Outcomes of Minors Worldwide

Abstract: Experiences of discrimination such as everyday racism can negatively affect the mental and physical health of children and adolescents with an immigrant background and impair their integration process in the host societies. Although experiences of racism are part of the everyday life of many minors affected by the process of “Othering” (e.g., those with an immigrant background), an overview of empirical findings is missing for this age group worldwide. A systematic review was conducted to identify and analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 73 publications
2
12
0
2
Order By: Relevance
“…The third hypothesis confirmed the existing relationship between discrimination and self-esteem. In line with many studies, discrimination was found to be a significant negative predictor of self-esteem [ 55 ]. Researchers have also found an association between racial discrimination and other outcomes among children and adolescents, e.g., well-being or health [ 56 , 57 ] and as a risk factor for depressive symptoms and substance abuse [ 58 ].…”
Section: Discussionsupporting
confidence: 85%
“…The third hypothesis confirmed the existing relationship between discrimination and self-esteem. In line with many studies, discrimination was found to be a significant negative predictor of self-esteem [ 55 ]. Researchers have also found an association between racial discrimination and other outcomes among children and adolescents, e.g., well-being or health [ 56 , 57 ] and as a risk factor for depressive symptoms and substance abuse [ 58 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our meta-analytical study is the first to consider an exclusive investigation of RD and suicidality and to perform two separate analyses measuring the effects of RD both on SI and on SA. Our study adds to the growing body of literature indicating that RD is pernicious to well-being and may be a driver of health disparities in society, as groups exposed to RD may exhibit accentuated decline in mental health parameters ( Coimbra et al, 2020 ; Kairuz et al, 2021 ; Metzner et al, 2022 ; Williams & Williams-Morris, 2000 ). As such, more awareness of the issue of RD and the appropriate development of more effective intervention strategies to tackle its effects should be a concern among health workers, researchers, educators, and policymakers.…”
Section: Discussionmentioning
confidence: 75%
“…Since previous studies, having examined the association between discrimination and mental health, have found significant correlations between these constructs [ 5 , 48 ], it must be assumed that discrimination not only has a short-term effect on the mood of those affected, but also can have an impact on their general mental health and well-being [ 5 , 48 ]. According to a current review, (racial) discrimination appears to be a key acculturative stress factor for adolescents, has effects on their mental and physical health and is associated with lower self-esteem and lower well-being [ 49 ]. Further findings of that review link perceived or experienced discrimination of immigrant children and adolescents to other developmental outcomes, e.g., a low ability to conduct for interpersonal relationships, misconduct or delinquency, a lower sense of mastery and control, higher substance use, as well as lower life satisfaction and sense of competence [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a current review, (racial) discrimination appears to be a key acculturative stress factor for adolescents, has effects on their mental and physical health and is associated with lower self-esteem and lower well-being [ 49 ]. Further findings of that review link perceived or experienced discrimination of immigrant children and adolescents to other developmental outcomes, e.g., a low ability to conduct for interpersonal relationships, misconduct or delinquency, a lower sense of mastery and control, higher substance use, as well as lower life satisfaction and sense of competence [ 49 ]. The relation of discrimination to greater physiological stress, depressive symptoms, and disruptive school behavior has also been shown in a German study among immigrant youth [ 50 ].…”
Section: Discussionmentioning
confidence: 99%